2012
DOI: 10.1371/journal.pone.0041784
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Physics Concepts: Concreteness and Presentation Modality Reflected by Human Brain Dynamics

Abstract: Previous research into working memory has focused on activations in different brain areas accompanying either different presentation modalities (verbal vs. non-verbal) or concreteness (abstract vs. concrete) of non-science concepts. Less research has been conducted investigating how scientific concepts are learned and further processed in working memory. To bridge this gap, the present study investigated human brain dynamics associated with encoding of physics concepts, taking both presentation modality and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(58 reference statements)
10
7
0
Order By: Relevance
“…The frontal midline theta was activated at the first stimulus and sustained the power activation during the subsequent stimulus presentations; it then slightly increased during the maintenance period and continued increasing the theta augmentation until the subjects responded. These patterns were consistent with previous studies which suggested that frontal theta activity is involved with the active maintenance of working memory information until the information is retrieved [ 26 , 27 , 31 , 32 ] or until the execution of cognitive controls, such as rehearsal or focused attention [ 28 , 60 ]. On the other hand, the occipital and central parietal regions showed pronounced theta power augmentation after stimuli and probe presentation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The frontal midline theta was activated at the first stimulus and sustained the power activation during the subsequent stimulus presentations; it then slightly increased during the maintenance period and continued increasing the theta augmentation until the subjects responded. These patterns were consistent with previous studies which suggested that frontal theta activity is involved with the active maintenance of working memory information until the information is retrieved [ 26 , 27 , 31 , 32 ] or until the execution of cognitive controls, such as rehearsal or focused attention [ 28 , 60 ]. On the other hand, the occipital and central parietal regions showed pronounced theta power augmentation after stimuli and probe presentation.…”
Section: Discussionsupporting
confidence: 92%
“…Meltzer et al reported that the theta and alpha increases in the frontal midline cortex while the alpha decreases in the occipital cortex during a working memory operation [ 30 ]. In addition, some studies have reported that frontal theta activities are involved in the memory encoding process and, furthermore, that parietal and occipital theta functions were associated with working memory tasks [ 19 , 31 , 32 ]. These studies reported very interesting temporal dynamic patterns during working memory tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2 , non-significant Add alpha activation was observed in the frontal component, and significant U-Add alpha activations were found in the posterior region (Wilcoxon signed-rank test, FDR-adjusted p < 0.05). Like the theta activation in the frontal area, the posterior alpha is also associated with cognitive processes and attentional demands (Klimesch et al, 1998 ; Foxe and Snyder, 2011 ; Lai et al, 2012 ; Lin et al, 2012a ). Due to resource competition between tasks, U-Add activation occurs when one task dominates most of the resources used (Anderson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sustained attention and decision making have been mainly associated with frontal theta oscillations (Lin et al, 2011 ; Borghini et al, 2014 ). Alpha suppression in the posterior area, including the parietal and occipital regions, is also associated with attentional demands and cognitive progress (Klimesch et al, 1998 ; Foxe and Snyder, 2011 ; Lai et al, 2012 ). Through the experimental tasks and attentional demands, we focused on the brain dynamics in the frontal, parietal and occipital regions, which are highly correlated with attentional processes (Tachibana et al, 2012 ; Schweizer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have has widely discussed the link between the theta band and WM. Research [15,16] has also illustrated that the EEG patterns associated with the encoding of physics concepts in working memory revealed greater theta activity that was accompanied by the onset of a word stimulus rather than a picture stimulus. According to Norbert, the increase in theta synchronization means enhanced encoding, retrieval, and performance of the central executive and attention control [17].…”
Section: Link Between Eeg Rhythms and Working Memorymentioning
confidence: 99%